Policy analysis of micro Waqf banks in Indonesia - Muhammad Fikry Aransyah; Muhammad Noor; Amjad Hamad Abdullah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2022)
This article aims to understand the Indonesian Government's efforts in making policies to handle the development of micro Waqf banks in Indonesia. The handling strategy can be assessed by understanding the policies formulated and implemented by the Indonesian Government. This study used a deliberative policy analysis approach, and data were collected through a literature study. The results of this study conclude 1) management for groups that can avoid misuse of loan funds and disbursement of funds not on target; 2) training and mentoring can build management commitment and customer enthusiasm to build a more advanced business; 3) with the financing method without collateral, the Islamic financial system does not collect deposits, low yields, and fast and easy administrative processes such as Islamic banking. Combining these three factors optimizes the performance of the micro Waqf bank in economic empowerment and community productivity. It helps increase the income and welfare of the community around the pesantren (Islamic boarding school).